The Influence of Slang on the Indonesian Language Ability of Elementary School Students - Nasrul Haq, Muhammad (Lembaga Bale Literasi, 2025)
This study aims to analyze the impact of the use of slang on the Indonesian language ability of elementary school students. Informal slang that deviates from the rules of standard language is now widely used by students in their daily lives, both in direct communication and through social media. The method used is a literature study with a qualitative descriptive approach that refers to various relevant literature. The results showed that the intensive use of slang can lead to a decrease in mastery of standard vocabulary, difficulty in structuring sentences according to the correct structure, and confusion in distinguishing between formal and informal language contexts. Nevertheless, students still recognize the importance of Indonesian in the context of education and official communication. To overcome this negative impact, cooperation between teachers, parents, and the environment is needed in fostering good language habits, as well as the implementation of learning strategies that emphasize the importance of correct Indonesian as a means of communication and national identity.